Pemimpin Kristen Sebagai Agen Perubahan di Era Millenial - Suhadi Suhadi; Yonatan Alex Arifianto (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2020)
AbstractReal leadership begins with the person of a leader with a servant's heart, then is revealed to be outside serving others. It is Jesus who is a model role model for Christian leaders, so that Christian leaders are given the ability by God to bring about changes as God wants. Christian leaders are able to bring change for the better, more useful to God and others, because Christian leaders are agents of change in this Melenial era, who bring generations to understand new literacy and are not technology blind. This writing uses a literature research method with a descriptive qualitative approach, so that it can describe Christian leaders, by dividing the understanding of leaders specifically in Christian leadership. So that they can qualify Christian leaders and make leadership an agent of change in the ways and steps that Christian leaders take to become agents of change. Christian leadership can be a reference for advancing the millennial generation and being a role model through agents of change who can bring technology to become a necessity today Abstrak Kepemimpinan yang sesungguhnya dimulai dari diri pribadi seorang pemimpin dengan hati seorang hamba, kemudian dinyatakan keluar untuk melayani orang lain. Yesuslah yang menjadi model teladan bagi pemimpin Kristen, sehingga pemimpin Kristen diberikan kemampuan oleh Allah untuk membawa perubahan sesuai yang dikehendaki oleh Allah. Pemimpin Kristen mampu membawa perubahan kearah yang lebih baik, lebih berfaidah bagi Allah dan sesamanya, karena pemimpin Kristen adalah agen perubahan di era Melenial ini, yang membawa generasi mengerti literasi baru dan tidak buta teknologi. Penulisan ini menggunakan metode penelitian pustaka dengan pendekatan kualitatif deskriptif, sehingga dapat mendeskripsikan pemimpin Kristen, dengan pembagian pengertian pemimpin secara khusus dalam kepemimpinan Kristen. Sehingga dapat mengkualifikasi pemimpin Kristen dan menjadikan kepemimpinnan adalah sebuah agen perubahan dengan cara dan langkah yang dilakukan pemimpin kristen untuk menjadi agen perubahan. Kepemimpinan Kristen dapat menjadi acuan untuk memajukan generasi milenial dan menjadi teladan melalui agen perubahan yang dapat membawa teknologi menjadi sebuah kebutuhan masa kini.